(untitled) (Research, Society and Development, 2021)
With the advance of environmental degradation in the agreste region of Paraíba, the objective was to study the rural area of the municipality of Gado Bravo, located in the mesoregion of Agreste Paraíba. Carrying out a spatiotemporal study of the region’s environmental degradation, georeferencing the artesian wells contained in the municipality. During the study, we used Digital Image Processing techniques from the images obtained by the Landsat 5 and 8 satellites. We found with this study that the region has low levels of environmental degradation, even showing in certain regions, due to the decrease in agricultural exploitation regional, the regeneration of some areas. Dealing with underground water, it has great social and economic relevance, as it moves the entire economy of the municipality.